Preliminary Observations on Variability of Teak in India - Bedell, P. E. (Indian Forester, 1989)
Forest trees with wide geographic distribution develop inherent adaptations to factors of the environment at tbe site wbere tbey grow in order to survive in a given ecological nicbe. These adaptations which are the result of prevalent environment are controlled to a great extent by genetic potentialities. When a species is taken up for breeding work it is necessary to study these variations to draw up a strategy for improvement. As teak is a species with wide geographic distribution and is raised as plantations right from Kerala in the soutb to as far north as Uttar Pradesh, it wasdecided to make a preliminary study initially to be followed up later by a more detailed study of intra and interpopulation variations. The results of the preliminary studies are presented in this paper. As variations in seed biology was studied a little more in detail than otber characteristics, recommendations have been made on tbe pretreatment requirements of teak seeds collected from different seed sources and are presented in the form of a table. These recommendations are of practical importance for raising nursery seedlings.